The effect of agricultural subsidies on efficiency and productivity of farms: a literature review - Nagy Zsuzsanna; Надь Ж. (ФОП Сабов А. М., 2019)
Abstract. Agriculture is subsidised in one form or the other in most of the countries. Subsidies can be coupled to inputs and/or outputs. Since coupling subsidies distorts prices and makes the relevant market non-competitive, the recent tendency is to decouple subsidies. Decoupled subsidies should, by definition, not affect farmers’ short-term marginal production decisions if the markets are perfectly competitive, there are no economies of scale and producers are risk neutral. However, in practice, these conditions do not hold, and thus even decoupled subsidies may affect production decisions.
Вплив сільськогосподарських субсидій на ефективність і продуктивність господарств: огляд літератури
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00007679
Keywords: agricultural subsidy; agriculture; efficiency; productivity